Self-Acceptance Among Leprosy Patients: A Qualitative Exploration of Personal and Social Challenges - Kaleka, Videlis Rinto Baro; Damayanti, Yeni; Pello, Shella Christine (Journal of Health and Behavioral Science, 2025)
Leprosy is a disease that attacks the physical and psychological so that it can affect the quality of psychological well-being of leprosy patients. Several factors that can affect psychological well-being in leprosy patients, one of which is self-acceptance. This study aims to provide an overview of self-acceptance of leprosy patients at the Bunda Pembantu Abadi Naob Hospital. The research design used qualitative research with 5 subjects with criteria determined by purposive sampling techniques, namely leprosy patients who were undergoing treatment at the Hospital. The data collected were analyzed using thematic analysis techniques and produced 3 main themes, namely, psychological impacts, self-acceptance factors, and treatment challenges. Self-acceptance of leprosy patients is explained through various psychological impacts experienced by leprosy patients, namely stigma and rejection and various negative feelings about themselves, also through various factors that encourage leprosy patients to achieve self-acceptance, namely motivation, treatment in the hospital as a new hope, religious coping, and social support. In the process of achieving healing and self-acceptance, there are challenges faced by leprosy patients, namely lack of knowledge about the disease, misdiagnosis, and traditional medicine. In addition to providing physical therapy services, in the future hospitals need to develop psychosocial support programs to improve self-acceptance and psychological well-being of leprosy patients.